Modelos de mistura para avaliação de produtos e serviços - Polli, Démerson André (Universidade Federal de São Carlos, 2019)
The product (or services) evaluation is a necessity in many steps of the development and release of such producs (services). The product evolution and the market share definition are two steps that evolves some kind of evaluation. Although, the evaluation occur by assigning grades not related with the perception of the product (service) quality –assigning values at random. This work presents 4 new models, 2 of them based on the CUB (Combined Uniform and shifted Binomial) model, for evaluation of items where there are two or more levels of preference by the evaluators and may have evaluators assigning grades at random.
Mixture models for products and services evaluation
Keywords: avaliação de produtos; Avaliação de serviços; Modelos de mistura finita; Distribuições discretas de probabilidade; Product evaluation; Finite mixture models; Discrete distributions; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA